A Perspective Approach to Study the Valency-Based Irregular Indices for Benzenoid Planar Octahedron Structures - Maria Singaraj Rosary; Ammar Alsinai; Mohammad Kamran Siddiqui; Hanan Ahmed (Journal of Chemistry)
The molecular topology and the chemical structures which are not regular perform a dominant character in designing the compound in connection with their physical and chemical properties. The study of topological descriptors of molecular structures is widely used in the field of cheminformatics, information technology, biomedical science, and many more. Numerous topological indices have been evolved in the theory of chemistry. Graphs which are not regular can be specified using irregular measures. In this article, we find some irregularity indices, which are useful in Quantitative structure activity relationship for benzenoid structures. Based on the exact analytic expressions, the numerical and graphical comparison for benzenoid structures is also provided.